Inventarisasi dan Identifikasi Kumbang Koksi (Coleoptera:Coccinellidae) pada Tanaman Solanaceae di Kabupaten Ogan Ilir, Sumatera Selatan - Figo Ardatha Sutarma; Ade Gilang Rhomadon; Muhammad Ryan Asrul; Desi Fitriyani; Fuan Ambar Rahma; Hanny Lia Anggraini; Abu Umayah; Bambang Gunawan; Arsi Arsi (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2023)
Sutarma FA, Rhomadon AG, Asrul MR, Fitriyani D, Rahma FA, Anggraini HL, Umayah A, Gunawan B, Arsi A. 2022. Inventory and identification of ladybug (coleoptera: coccinellidae) on solanaceae crops in Ogan Ilir Regency, South Sumatra. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 450-457. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The ladybug (Coleoptera: Coccinellidae) is considered to have an influence on the cultivation of solanaceae crops because there are many types as biological control agents for plant pests and as phytophagous insects. The purpose of this study was to determine the types of ladybugs on Solanacae crops in Ogan Ilir Regency, South Sumatra, Indonesia. The sampling method used 2 techniques with insect nets swinging infinity on the plant canopy and direct collection techniques, namely taking directly by hand. Sampling of the ladybug in the field was carried out 3 times in each field. Sampling of the ladybug was carried out in the morning at around 07.00-10.00 am. Based on the results of sampling in the field, the beetles found were Coccinella sexmaculata, Verania discolor, V. lineata, C. repanda, and Epilachna admirabilis. This ladybug has different morphological characteristics, body size, and distribution between predatory ladybugs and phytophagous ladybugs. The species of ladybug that acts as a natural enemy is most commonly found in chili plantations. The predatory ladybug can control the attack of A. gossypii on eggplant and chili plantations. Coccinellidae phytophagous is a plant-eating ladybug that is commonly found in eggplant plantations. The conclusion in this observation is that there are 5 species of ladybug, 4 predatory ladybugs and 1 phytophagous ladybug. Research related to the identification and inventory of the ladybug (Coleoptera: Coccinellidae) needs to be improved as information on the types of ladybug species is useful in the management of solanaceae cultivation in order to further increase solanaceae crop yields in Ogan Ilir Regency.